AFTA and liberlization of financial services in the Lao PDR - Xayleuxa Phouyavong; Swierczek, Fredric W.; Zimmermann, Willi; Tang, John C.S.; Asian Development Bank-Japan Scholarship Program (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
This research studied the readiness of the Lao PDR to liberalize its financial sector under ASEAN Free Trade Area (AFTA). It also analyzes the benefits and costs that Laos PDR will have if it opens the financial sector. The Lao PDR presently still has a problem in macro economic management that influences negatively to the banking sector. The Lao financial industry is not diversified, the large market shares are held by three state owned banks, and the most of them are weak in tern of management. Banking products are limited compared to the banking industry in some other countries in this region, and Lao banking industry development is far behind them. The study also found that the main problem of Lao the banking sector is credit management in state owned banks, weak bank supervision creates risk for financial liberalization if those problems are not solved before opening the sector. The Lao banking sector needs some time to improve itself in order to compete with foreign institutions inside the country and overseas. The state has to strengthen fiscal budget and effectively implement monetary policy to maintain economic stability
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2006
Keywords: Free trade -- Laos; Financial services industry -- Laos; ASEAN Free Trade Area